IMPLEMENTASI AJARAN ASIH DALAM TRI PARARTHA: UPAYA REVITALISASI SIKAP TOLERANSI GENERASI Z - I Made Sidia; I Nengah Juliawan; Ni Kadek Rika Pramestika Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Education, economy, science and technology have experienced significant changes, this has an influence on all aspects of people's lives, especially in the order of individual behavior both positively and negatively. In order to create harmony in social behavior to respond to this development, it is necessary to have a conceptual context that is used as a guide or attitude, one of which is Asih which is love or compassion in Tri Parartha can be implemented by generation Z with supporting factors, namely the teachings of Tat Twam Asi, which means I am you, you are me. Tat Twam Asi's teachings teach to treat others the way you want to be treated. As for the example of the implementation of Asih's teachings, getting used to saying greetings, bowing when passing other people or older people as a form of respect and appreciation. In addition, Asih's teachings can be implemented through the local wisdom of Hindus in Bali, namely Manyama Braya or Matetulung. Through this concept, the younger generation, especially Generation Z today, can learn about respecting differences and placing others as family so that the spirit of tolerance remains.Keywords: Asih, Tri Parartha, Tolerance, Generation Z